Features of the relationship between emotional burnout and experiencing psychological stress with socio-psychological factors, anxiety-depressive and asthenic manifestations in medical workers during the COVID-19 pandemic - R. I. Antokhina; A. V. Vasilyeva; E. Y. Antokhin; L. S. Chutko; N. V. Stepanova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The purpose of the study: to study the relationship between emotional burnout and the experience of psychological stress with socio-psychological factors, anxiety-depressive and asthenic manifestations in medical workers during the pandemic of a new coronavirus infection.   227 medical workers were studied using a socio-psychological questionnaire, the Questionnaire of emotional burnout by K. Maslach, the A. Beck Depression Scale, the A. Beck Anxiety Scale, the Visual Analogue Fatigue Scale, the PSM-25 Psychological Stress Scale. The results of the study reveal conflicting attitudes of medical staff towards COVID-19. Psychological distress was revealed in more than a third of those studied in the form of a decrease in emotional tone, increased mental exhaustion, a decrease in interest and positive feelings for others, a feeling of «satiation» with work, dissatisfaction with life in general, and emotional withdrawal. Nearly a quarter of healthcare workers report signs of depression. 30% of respondents experience a fairly high level of fatigue. Doctors are the most emotionally exhausted of all the examined specialists. Doctors and medical psychologists have more pronounced depressive manifestations, depreciation of interpersonal relationships than junior staff. A more pronounced reduction in personal achievements was found in women than in men, and in men, somatic manifestations of depression and fatigue were more pronounced. A greater subjective saturation of experiences for medical workers during a pandemic is caused by the fact that they suffered COVID-19 in their relatives than in themselves.   Conclusions. There is a certain similarity in the emotional response to stressful situations during the COVID-19 pandemic among doctors and clinical psychologists, in contrast to nurses and orderlies. A COVID-19 infection in loved ones is stressful for healthcare professionals. Gender is associated in different ways with manifestations of psychological stress in medical professionals with a predominance of astheno-depressive manifestations in men and a decrease in confidence in professional competence in women.